Synthesis of high quality hydrothermally grown ZnO nanorods for photoelectrochemical cell electrode. Issue 10 (15th May 2021) - Tan, Huey Jing; Zainal, Zulkarnain; Talib, Zainal Abidin; Lim, Hong Ngee; Shafie, Suhaidi; Tan, Sin Tee; Tan, Kar Ban; Bahrudin, Noor Nazihah
Abstract: One-dimensional ZnO nanorods (ZnO NRs) have the edge over other nanostructures due to their unique properties. Current work fabricated ZnO NRs on pre-seeded ITO glass substrate through hydrothermal synthesis using customized hydrothermal set-up. The sources of Zn 2+ and OH − ions were supplied continuously from zinc nitrate hexahydrate and hexamethylenetetramine (HMTA), respectively whereby the concentration of both precursors and the temperature of growth solution varied from 0.01 M to 0.05 M and from 80 °C to 120 °C, respectively. The impact of concentration and temperature variation on hydrothermal reaction and corresponding PEC cell performance is discussed. Field emission scanning electron microscopy (FESEM) results revealed that the morphology of prepared ZnO NRs arrays is concentration- and temperature-dependent. X-ray diffraction (XRD) reflected strong orientation along (002) direction for the hexagonal wurtzite ZnO NRs, and the film crystallinity greatly improved when the temperature increased. At optimal concentration and hydrothermal temperature, the ZnO NRs photoanode exhibited a bandgap value of 3.22 eV and achieved an impressive photocurrent density of 0.483 mA/cm 2 that was attributed to the ordered rods alignment and improved optical properties. In addition, the electrochemical impedance spectroscopy (EIS) demonstrated optimized one-dimensional (1D) NRs sample showed better charge separation and transfer rate, which was two times larger than ZnO nanoparticles. The present work exhibited better photoelectrochemical performance than the other reported literature showing the high quality of ZnO NRs produced. Graphical abstract: Illustration on the effect of hydrothermal conditions on ZnO NRs growth and PEC performance. Image 1